Overview Of Knowledge About Post-Placental Iud Among Women of Reproductive Age in Maguwoharjo Village, Sleman - Indah Purnamasari; Indah Fitri Agustina; Muntiyati Erna Susilowati (CV. AFDIFAL MAJU BERKAH, 2025)
Population growth remains one of the most significant global challenges, particularly in developing countries. To address this issue, family planning programs play a crucial role, one of which is the use of post-placental intrauterine devices (IUDs). Post-placental IUDs offer many advantages, including high effectiveness, immediate accessibility after delivery, safety for breastfeeding mothers, and rapid return of fertility after removal. However, the utilization rate of this contraceptive method remains low, often due to limited knowledge among women of childbearing age. Adequate knowledge is essential to encourage informed decision-making regarding contraceptive use. This study aimed to describe the level of knowledge about post-placental IUDs among women of childbearing age. A descriptive research design was used, involving 78 respondents who met the inclusion and exclusion criteria. Data were collected using a structured questionnaire on post-placental IUD knowledge and analyzed using descriptive statistics. The findings revealed that only 2 respondents (2.6%) demonstrated good knowledge, 43 respondents (55.1%) had fair knowledge, and 33 respondents (42.3%) exhibited poor knowledge regarding post-placental IUDs. The majority of respondents thus had a fair level of knowledge, indicating partial awareness but limited comprehensive understanding of this contraceptive method. These results highlight the need for improved health education strategies, particularly by healthcare providers, to enhance women’s knowledge and promote the adoption of post-placental IUDs. Strengthening information delivery may contribute to increased utilization and ultimately support population control efforts.